PENGARUH E-LKPD BERBASIS LITERASI NUMERASI TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS V SD NEGERI 2 KOTA GAJAH - Eliya Roissatul Khusnia; Siska Mega Diana; Deviyanti Pangestu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem in this study was the low critical thinking skills of fifth-grade students at SD Negeri 2 Kota Gajah. The research was conducted to determine the effect of using numeracy literacy-based E-LKPD (Electronic Student Worksheets) in mathematics on the critical thinking skills of fifth-grade students at SD Negeri 2 Kota Gajah. The method used was a quasi-experimental design with a non-equivalent Control Group Design. Data collection techniques included essay tests and non-test methods (observation). Hypothesis testing was performed using simple linear regression. A significance value of 0.000 (< 0.05) and an F-calculated value of 31.416 (F > F-table 4.381) were obtained, leading to the acceptance of the alternative hypothesis (Ha). Therefore, it was concluded that there was a significant influence of using numeracy literacy-based E-LKPD in mathematics on the critical thinking skills of fifth-grade students at SD Negeri 2 Kota Gajah.